Cervical Epidural Anesthesia for Carotid Endarterectomy (Cardiovascular Journal, 2010)
The successful anaesthetic management using a cervical epidural technique is reported in patients undergoing carotid artery surgery. Adequate analgesia is obtained and the adequacy of cerebral blood flow is easily judged by the patient’s state of consciousness. Cervical epidural anaesthesia could be a safe and reasonable technique for the management of patients who need carotid artery surgery.A 54 years old man of A.S.A (American Society of Anesthesiologists) grade- II underwent carotid endarterectomy under Cervical Epidural Anaesthesia (CEA) at C7 – T1 level using a mixture of 0.5% Lidocaine, 0.25% Bupivacaine and Fentanyl citrate. Standard peroperative monitoring including invasive arterial blood pressure and arterial blood gas analysis was done. Keywords: Cervical epidural Anaesthesia; Carotid Endarterectomy; Monitoring of cerebral function DOI: 10.3329/cardio.v2i2.6650Cardiovasc. j. 2010; 2(2) : 256-257